ANALISIS PENERAPAN KESELAMATAN KERJA MENGGUNAKAN METODE HAZARD IDENTIFIKACATION RISK ASSESSMENT (HIRA) - Sri Mayasari; Bagus Andika Fitroh; Adib Norma Respati Respati (Jurnal Ilmiah Dinamika Teknik, 2020)
Abstract This study was aimed the risk source, to evaluate, and apply K3 (occupattional health and safety) system of Anugrah Batik Industry. The research was conducted with observation in the Anugrah Batik Industry Laweyan Solo with 20 of employee and data collection were interview and take the picture that using as data processing. The data observed is identification of the dangerous potension in Anugrah Batik Industry consist: membatik, nglorot, mbironi, washing of the batik cloth, and risk assessment. The result of the study showed that risk control before carried out the application of K3 many found dangerous event can to be injuring for body of the employee. It could be concluded that risk control to minimize the potension of danger can be done by addition APD, so that the result of the risk assessment after applied the value potension of danger on batik activity can be minimized. Keywords: Risk Assessment, Mbatik, Nglorot, Mbironi, Wasing batik cloth